Developing catalytic materials for the oxidative coupling of methane through statistical analysis of literature data. Issue 3 (18th December 2014) - Kondratenko, Evgenii V.; Schlüter, Michael; Baerns, Manfred; Linke, David; Holena, Martin
Abstract : Accuracy of models based on literature data for predicting experimental yield of C2 hydrocarbons over La2 O3 - and MgO-based catalysts in the oxidative coupling of methane. Abstract : Based on available 1870 literature data for the oxidative coupling of methane (OCM), various statistical models were applied i) to design three-component catalysts consisting of one host metal oxide (La2 O3 or MgO) and two oxide (Li, Na, Cs, Sr, Ba, La, or Mn) dopants and ii) to predict their OCM performance. To validate this approach for catalyst design, selected materials were prepared and experimentally tested for their activity and selectivity in the target reaction. The effects of kinds of host oxides, dopants and their interplay on the OCM performance of differently composed catalysts were statistically evaluated.